Razvoj in uporaba metode za spremljanje velikosti populacije velikonočnice (Pulsatilla grandis) - Kalan, Gregor (Varstvo narave, 2010)
The paper discusses the method designed for the Pasque Flower (Pulsatilla grandis) population size monitoring. The method has been developed on the basis of a prolonged monitoring of the changes in the Pasque Flower populationsize at Boletina near Ponikva. The census carried out according to this method provided us with the flowerćs first population estimates, by whichthe morphological characteristic that a single Pasque Flower can have several flowering shoots was taken into account. The results of the censuses carried out so far (1,218 plants on average) are also given. In 2007, fewer flowering plants in comparison with previous years (485 plants) were established, presumably as a result of milder temperatures in the preceding winter. The paper further presents the obligatory elements of the annual report on the monitoring of the Pasque Flower abundance and the fieldwork survey sheet.
Keywords: botanika; environmental protection; populacije; Pulsatilla grandis; Rhododendron-Park Bremen; varstvo narave; velikonočnica